Adult Sox2+ stem cell exhaustion in mice results in cellular senescence and premature aging. Issue 5 (20th August 2018) - Vilas, Jéssica M.; Carneiro, Carmen; Da Silva‐Álvarez, Sabela; Ferreirós, Alba; González, Patricia; Gómez, María; Ortega, Sagrario; Serrano, Manuel; García‐Caballero, Tomás; González‐Barcia, Miguel; Vidal, Anxo; Collado, Manuel
Abstract: Aging is characterized by a gradual functional decline of tissues with age. Adult stem and progenitor cells are responsible for tissue maintenance, repair, and regeneration, but during aging, this population of cells is decreased or its activity is reduced, compromising tissue integrity and causing pathologies that increase vulnerability, and ultimately lead to death. The causes of stem cell exhaustion during aging are not clear, and whether a reduction in stem cell function is a cause or a consequence of aging remains unresolved. Here, we took advantage of a mouse model of induced adult Sox2+ stem cell depletion to address whether accelerated stem cell depletion can promote premature aging. After a short period of partial repetitive depletion of this adult stem cell population in mice, we observed increased kyphosis and hair graying, and reduced fat mass, all of them signs of premature aging. It is interesting that cellular senescence was identified in kidney after this partial repetitive Sox2+ cell depletion. To confirm these observations, we performed a prolonged protocol of partial repetitive depletion of Sox2+ cells, forcing regeneration from the remaining Sox2+ cells, thereby causing their exhaustion. Senescence specific staining and the analysis of the expression of genetic markers clearly corroborated that adult stem cell exhaustion can lead to cellular senescence induction and premature aging.